Optimising Time Efficiency in Green Retrofit Jetty Projects through Envision and Lean-Based Value Stream Mapping - Aprilian Ismana; Mawardi Amin; Pio Ranap Tua Naibaho; Deprizon Syamsunur (Advance Sustainable Science Engineering and Technology, 2026)
Indonesia, as a strategic global maritime axis, has only 7.03% of its islands equipped with jetties, and jetty construction poses environmental challenges due to emissions and ecological impacts. Green retrofitting provides a sustainable solution by improving energy efficiency in existing jetties. The Envision rating system guides the transition from conventional to green infrastructure, assessing quality of life, leadership, resource allocation, natural environment, and climate resilience. Despite its benefits, 32% of green projects experience delays. This study analyzes the key factors influencing time performance optimization in Green Retrofit Jetty projects using Lean–Value Stream Mapping (VSM). Using SEM-PLS, ten critical factors were identified. Lean–VSM facilitates process visualization and waste elimination. The Green Retrofit Jetty, achieving an Envision Platinum rating, reduced project duration from 250 to 220 days, demonstrating a 12% improvement in time performance while supporting efficient and sustainable jetty development.